Does Voluntary Risk Taking Affect Solidarity? Experimental Evidence from Kenya - Renate Strobl; Conny Wunsch (Institute of Labor Economics (IZA), 2017)
In this study we experimentally investigate whether solidarity, which is a crucial base for informal insurance arrangements in developing countries, is sensitive to the extent to which individuals can influence their risk exposure. With slum dwellers of Nairobi our design measures subjects' willingness to share income with a worse-off partner both in a setting where participants could either deliberately choose or were randomly assigned to a safe or a risky project. We find that when risk exposure is a choice, willingness to give is roughly 9 percentage points lower compared to when it is exogenously assigned to subjects. The reduction of solidarity is driven by a change in giving behaviour of persons with the risky project. Compared to their counterparts in the random treatment, voluntary risk takers are seemingly less motivated to share their high payoff with their partner, especially if this person failed after choosing the risky project. This suggests that the willingness to show solidarity is influenced by both the desire for own compensation and attributions of responsibility. Our findings have important implications for policies that interact with existing informal insurance arrangements.
Keywords: D81; C91; O12; D63; 330; solidarity; risk taking; Kenya